2007
DOI: 10.5039/agraria.v2i3a22
|View full text |Cite
|
Sign up to set email alerts
|

Adubação potássica na cultura da soja em duas épocas de semeadura

Abstract: entressafra (08/05/00) e o outro em época convencional, na safra de verão (27/11/00); em ambos se avaliaou o comportamento das variedades de soja: Conquista (MG/BR 46) e Liderança (MG/BRS 66), submetidas a 4 doses de potássio (0, 40, 80 e 160 kg ha -1 de K 2 O). Utilizou-se delineamento experimental em blocos casualizados com quatro repetições, cujos tratamentos se dispunham em um esquema fatorial 2 x 4 (variedades e doses), em cada época de semeadura. Nas duas épocas de semeadura as variedades diferiram signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
1
3
1
2
Order By: Relevance
“…These data corroborate those obtained by Gonçalves et al (2010), who found an increase iof the number of pods plant -1 with the application of 60 kg ha -1 K 2 O, however, this results differ from Aratani et al (2007), who noticed no effect of increasing K doses. This difference in results can be attributed to the edaphic and climatic conditions of each region, since in both studies, K levels were considered as average, with 68 mg dm -3 and 70 mg dm -3 , respectively.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…These data corroborate those obtained by Gonçalves et al (2010), who found an increase iof the number of pods plant -1 with the application of 60 kg ha -1 K 2 O, however, this results differ from Aratani et al (2007), who noticed no effect of increasing K doses. This difference in results can be attributed to the edaphic and climatic conditions of each region, since in both studies, K levels were considered as average, with 68 mg dm -3 and 70 mg dm -3 , respectively.…”
Section: Resultssupporting
confidence: 66%
“…These results differ from those experienced by Lana, Hamawaki, Lima and Zanão Júnior (2002) for dry biomass, however, corroborate those obtained by Aratani, Lazarini and Marques (2007), Moterle et al (2009) and Gonçalves Junior, Nacke, Marengoni, Carvalho, and Coelho (2010) for height, number of pods plant -1 , number of seeds pod -1 and a thousand seeds weight. As for productivity, results are inconsistent, since, in some studies (Foloni & Rosolem, 2008;Guareschi et al, 2008) there was response to the productivity in function of application periods, while in other studies, no answer has been verified (Aratani et al, 2007;Bernardi et al, 2009 ns -not significant; DAS -days after sowing; IENU -internal efficiency nutrients use -potassium; IGH -index of grain harvest.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…Por isso, trabalhos são realizados visando encontrar doses e formas adequadas de aplicação dos corretivos para cada tipo de cultivo. Os macronutrientes aplicados à cultura da soja são bem estudados, com diversas pesquisas realizadas no intuito de melhorar a eficiência na utilização desses nutrientes (Mascarenhas, et al 2000;Aratani et al, 2007;Moterle et al, 2009;Oliveira Júnior, et al, 2011) o mesmo não sendo observado em relação aos micronutrientes.…”
Section: Introductionunclassified
“…However, due to the high degree of weathering Cerrado soils have low K content, and the natural reserves of this nutrient do not support successive edamame crops. This makes it necessary to return and supplement this nutrient through K fertilization (Aratani et al, 2007).…”
mentioning
confidence: 99%